Faktor-Faktor Yang Memengaruhi Kepatuhan Perawat terhadap Standar Operasional Prosedur (SOP) Perioperatif untuk Mencegah Infeksi Luka Post Operasi di RSUD Dr. R. Goeteng Taroenadibrata Purbalingga - Yuni Sukma Panca Indrawati; Yunita Sari; Annas Sumeru (Journal of Bionursing, 2023)
Background. In preventing the incidence of Surgical Site Infection (SSI), nurse compliance in carrying out perioperative care according to procedures is important. Knowledge, work period, workload, and role of the head of the room probably relate to nurse compliance. The purpose of this research is to analyze the relationship between knowledge, work period, workload, and role of the head of the room with nurse compliance and to know the dominant factor affecting nurse compliance in implementing perioperative SOP to prevent postoperative wound infections. Methods. The research design was correlated with cross-sectional approach. The population in this research is all nurses in the surgical and obstetric-gynecology wards of Dr. R. Goeteng Taroenadibrata Purbalingga Hospital. The total number of samples was 55 respondents. Collecting data using questionnaires. Results. Bivariate analysis showed that there was a significant correlation between knowledge, workload, and role of the head of the room with nurse compliance in implementing perioperative SOP. Meanwhile, there was no correlation between work period and nurse compliance in impelementing SOP. Conclusion. Workload is the most dominant factor related to nurse compliance in implementing perioperative SOP.